(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article describes the effects of smoking on the body and the effect of nicotine alkaloids on the digestive system. Nicotine alkaloid affects almost all organs. In particular, food has a harmful effect on the organs of the digestive system, causing organ dysfunction, cell necrosis, and changes in the amount of organic substances in the organs.